Facial Volume Restoration with Permanent Dermal Filler (Artecoll-4) in Chinese Women - Li, Dong; Luo, Sheng-Kang; Wang, Yi-Chao; Lemperle, Gottfried (Facial Plastic Surgery, 2017)
Artecoll is the only permanent dermal filler to be approved by the European Union and China Food and Drug Administration, and has been used worldwide since 1994 in approximately 400,000 patients. Since 2002, Artecoll-4 has also been injected in China in more than 42,000 patients in more than 100 hospitals, primarily for beauty refinement in younger patients and for rejuvenation of the aging face. Artecoll-4 consists of polymethylmethacrylate (PMMA) microspheres (20% by volume) 40 µm in diameter, suspended in 3.5% bovine collagen solution and 0.3% lidocaine. The collagen carrier is absorbed rather early after injection and is completely replaced by the patient's own connective tissue within the first 3 months. Thus, in contrast to all other fillers, Artecoll-4 becomes the patient's own tissue, and it is a “living implant.” In this study, a total of 10,725 patients were treated in 25 Chinese cosmetic hospitals between 2007 and 2012. Optimal injection techniques, efficiency and lasting duration, complications, safety, outcome, and statistical results are discussed. The data support the safety and efficiency of large volumes of Artecoll-4 (5–10 mL) injected deep into the faces of Chinese women, who seek to have a smooth oval face without indentations. No foreign body granulomas have been reported since the recommendation for strict epiperiosteal injections. Level of evidence is Level IV, multiple center study.
Keywords: dermal filler; Artecoll-4; facial volume; facial rejuvenation; Chinese women